PHOSPHATASE ACTIVITY OF FOREST CHESTNUT AND CARBONATE SOILS, NONINFECTED AND INFECTED BY BACILLUS THURINGIENSIS BERLINER BACTERIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
It have been studied the influence of new form of insectine (titr 60 mid spor/g) on phosphotase activity of forest chestnut and carbonate soils. It has been shown that low insectine treatment doesn’t influence while high treatment even increases the phosphatas activity of investigated soils.